1997
DOI: 10.1038/39899
|View full text |Cite
|
Sign up to set email alerts
|

Absence of excitotoxicity-induced apoptosis in the hippocampus of mice lacking the Jnk3 gene

Abstract: Excitatory amino acids induce both acute membrane depolarization and latent cellular toxicity, which often leads to apoptosis in many neurological disorders. Recent studies indicate that glutamate toxicity may involve the c-Jun amino-terminal kinase (JNK) group of mitogen-activated protein (MAP) kinases. One member of the JNK family, Jnk3, may be required for stress-induced neuronal apoptosis, as it is selectively expressed in the nervous system. Here we report that disruption of the gene encoding Jnk3 in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
681
6
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,152 publications
(721 citation statements)
references
References 31 publications
27
681
6
7
Order By: Relevance
“…One model routinely used to investigate such phenomenon is the triggering of seizures with Kainic acid (KA), a marine‐derived amino acid that has a very high activating potential of glutamate transporters 38, 39, 40, 41. Several molecules acting downstream of the EGFR have been implicated in mediating KA‐induced neurotoxicity 42, 43. KA elicits seizures by direct stimulation of glutamate receptors, and indirectly by increasing the release of excitatory amino acids from nerve terminals 40.…”
Section: Resultsmentioning
confidence: 99%
“…One model routinely used to investigate such phenomenon is the triggering of seizures with Kainic acid (KA), a marine‐derived amino acid that has a very high activating potential of glutamate transporters 38, 39, 40, 41. Several molecules acting downstream of the EGFR have been implicated in mediating KA‐induced neurotoxicity 42, 43. KA elicits seizures by direct stimulation of glutamate receptors, and indirectly by increasing the release of excitatory amino acids from nerve terminals 40.…”
Section: Resultsmentioning
confidence: 99%
“…Even in the complete absence of c-Fos and c-Jun in double knockout mouse embryos, no defects in the normally occurring developmentally programmed cell death were recorded (Ro er-Tarlov et al, 1996). Consistently, mutant mice de®cient in either the jnk1, jnk2, or jnk3 genes are viable and develop normally (Dong et al, 1998;Yang et al, 1997b;. However, in a recent study, in which dual JNK knockouts were generated, it was found that the dual de®ciency of JNK1 and JNK2 causes embryonic lethality due to severe dysregulation of apoptosis during brain development (Kuan et al, 1999).…”
Section: Jun As a Mediator Of Apoptosismentioning
confidence: 97%
“…In contrast, mutant mice lacking either JNK1, or JNK2, or JNK3 develop without obvious structural abnormalities. However, JNK1 as well as JNK2 mutant mice exhibit decreased activation-induced Tcell death and imbalance between T H 1 and T H 2 mediated immune responses (Dong et al, 1998;Sabapathy et al, 1999;Yang et al, 1997bYang et al, , 1998. In Drosophila, evidence has been presented for an involvement of Jun in several developmental processes.…”
Section: C-jun and Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence that the JNK pathway is pro-apoptotic derives from studies that show that these kinases are activated rapidly in cells destined to undergo an apoptotic response, that their overexpression results in apoptosis in some cells, that anti-sense inhibition or the use of dominant negative constructs attenuates the apoptotic response, and in a recent publication by the use of a knock-out mouse Brenner et al, 1997;Butter®eld et al, 1997;Cardone et al, 1997;Chen et al, 1996a,b;Chuang et al, 1997;Frisch et al, 1996;Goillot et al, 1997;Seimiya et al, 1997;Verheij et al, 1996;Xia et al, 1995;Yang et al, 1997a;Zanke et al, 1996). In the latter studies, in mice de®cient in JNK3, which is restricted to the brain, there was a reduction in seizure activity and hippocampal apoptosis in response to the excitotoxic glutamate-receptor agonist kainic acid (Yang et al, 1997a).…”
Section: Jnks and Apoptosismentioning
confidence: 99%